The role of the general practitioner in multidisciplinary teams: a qualitative study in elderly care - Grol, Sietske M. (BMC Fam Pract, 2018)
BACKGROUND: In the western world, a growing number of the older people live at home. In the Netherlands, GPs are expected to play a pivotal role in the organization of integrated care for this patient group. However, little is known about how GPs can play this role best. Our aim for this study was to unravel how GPs can play a successful role in elderly care, in particular in multidisciplinary teams, and to define key concepts for success. METHODS: A mixed qualitative research model in four multidisciplinary teams for elderly care in the Netherlands was used. With these four teams, consisting of 46 health care and social service professionals, we carried out two rounds of focus-group interviews. Moreover, we performed semi-structured interviews with four GPs. We analysed data using a hybrid inductive/deductive thematic analysis. RESULTS: According to the health care and social service professionals in our study, the role of GPs in multidisciplinary teams for elderly care was characterized by the ability to ‘see the bigger picture’. We identified five key activities that constitute a successful GP role: networking, facilitating, team building, integrating care elements, and showing leadership. Practice setting and phase of multidisciplinary team development influenced the way in which GPs fulfilled their roles. According to team members, GPs were the central professionals in care services for older people. The opinions of GPs about their own roles were diverse. CONCLUSIONS: GPs took an important role in successful care settings for older people. Five key concepts seemed to be important for best practices in care for frail older people: networking (community), facilitating (organization), team building (professional), integrating care elements (patient), and leadership (personal). Team members from primary care and social services indicated that GPs had an indispensable role in such teams. It would be advantageous for GPs to be aware of this attributed role. Attention to leadership competencies and to the diversity of roles in multidisciplinary teams in GP training programmes seems useful. The challenge is to convince GPs to take a lead, also when they are not inclined to take this role in organizing multidisciplinary teams for older people.